Financial Analysis of 30.7 kW On Grid Rooftop PLTS in BLK Sukabumi Regency - Marina Artiyasa; Ajat; Anang Suryana; Gina Syabani Yuda (Nusa Putra University, 2024)
The use of solar energy as a solar power plant (PLTS) has increasingly developed and received attention in the last few decades. BLK Sukabumi Regency has a building roof that has the potential to be used as a rooftop PLTS, so it can reduce electricity bills. This research aims to financially analyze the integration of rooftop solar PV at the Sukabumi Regency Job Training Center (BLK). In this research, planning and design of a rooftop PLTS with a capacity of 30.7 kW was carried out using Canadian Solar 320 W solar panels and an ICA Solar 30 kW inverter. The analysis results show that the construction of this rooftop PLTS requires initial investment costs of IDR 300,000,000.00 with annual operational costs reaching IDR 35,278,070.00 and total operational and maintenance costs for 20 years reaching IDR 558,453,870.40. Apart from that, this project has a Net Present Cost (NPC) value of IDR 894,907,600.00 with a payback period of approximately 12 years. After integration with Rooftop PLTS, electricity tariffs succeeded in decreasing by around 30% from IDR 900/kWh to IDR 630.64/ kWh, with a reduction in energy costs from IDR 63,370,935.00/year to 30,615,359.59/year. Based on the results of this research, the relevant suggestions are: implementing a 30 kW rooftop PLTS in BLK Sukabumi Regency as a step towards more sustainable use of renewable energy; conduct further feasibility studies to find alternative components such as solar panels or inverters that are more economical without sacrificing system performance; and consider utilizing renewable energy in other locations on a larger scale, such as government buildings or large industries, to reduce dependence on fossil energy sources.